PENGARUH KECUKUPAN MODAL, RISIKO OPERASIONAL DAN KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN BUMN PERIODE 2010-2019 - Putri, Septiani Ananda; Pardistya, Irvan Yoga (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to determine the effect of capital adequacy, operational risk and non-performing loans on profitability in state-owned banks for the 2010-2019 period. This research uses purposive sampling method by taking a sample of 4 banks taken from www.sahamok.net data. The data is obtained from the annual financial reports issued by state-owned banks by visiting the websites of each state-owned bank. The sample size is 32 of the total sample obtained from 4 banks. The analysis technique used in this research is multiple linear regression with a significance level of 5%. The results of this study partially (t test) show that Capital Adequacy (CAR) and Non-Performing Credit (NPL) have a positive and significant effect on profitability, while Operational Risk (BOPO) has a negative and significant effect on the profitability of BUMN banking in the 2010-2019 period. Simultaneously (F test) the Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO) and Non-Performing Loans (NPL) have the same effect on profitability.